1997
DOI: 10.1007/pl00009515
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Review of Techniques for Recording Respiratory Events at Rest and during Deglutition

Abstract: The coordination between swallowing and respiration is essential for safe feeding, and noninvasive feeding-respiratory instrumentation has been used in feeding and dysphagia assessment. Sometimes there are differences of interpretation of the data produced by the various respiratory monitoring techniques, some of which may be inappropriate for observing the rapid respiratory events associated with deglutition. Following a review of each of the main techniques employed for recording resting, pre-feeding, feedin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(47 citation statements)
references
References 43 publications
1
46
0
Order By: Relevance
“…The nasal thermistor would provide similar advantages and disadvantages as the nasal cannula since it is typically placed at the nares entrance. The temperature mode thermistor transduced tracing, however, may demonstrate an increase in temperature during a period of no nasal airflow secondary to warming to body temperature [30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The nasal thermistor would provide similar advantages and disadvantages as the nasal cannula since it is typically placed at the nares entrance. The temperature mode thermistor transduced tracing, however, may demonstrate an increase in temperature during a period of no nasal airflow secondary to warming to body temperature [30].…”
Section: Discussionmentioning
confidence: 99%
“…Given the advantages and disadvantages of the various techniques for recording respiratory events, the nasal cannula has been recommended and was used to record nasal airflow and SAD in this study [30].…”
Section: Discussionmentioning
confidence: 99%
“…18,19,27 The nasal airflow signal correlates well with recordings of rib cage and abdominal wall displacement during breathing 18,27 and has become the recommended technique for track- ing respiratory-related airflow during swallowing. 66 Further, we found that respiratory activity and videofluoroscopic swallowing signals can be synchronized and measured reliably using commercially available equipment during liquid swallowing. 19 The results of the current study point to the ease and accuracy of using a combined nasal airflow and swallowing recording system that accommodates most fluoroscopy units and suites.…”
Section: Commentmentioning
confidence: 97%
“…THE DETERMINATION of respiratory phases (inspiration and expiration) in relation to swallowing is integral to the study of the maturity and competence of the swallowing mechanism (SELLEY et al, 1994;TARRANT et al, 1997). During acoustical monitoring of swallowing, the respiratory phases may be determined by direct measurement of airflow using a pneumotachograph, nasal cannulae connected to a pressure transducer, heated thermistor anemometry, or by indirect means, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…During acoustical monitoring of swallowing, the respiratory phases may be determined by direct measurement of airflow using a pneumotachograph, nasal cannulae connected to a pressure transducer, heated thermistor anemometry, or by indirect means, i.e. detection of chest and/or abdominal movements using respiratory inductance plethysmography (RIP), strain gauges or magnetometers (TARRANT et al, 1997). The combined use of nasal cannulae connected to a pressure transducer in addition to measurement of respiratory inductance to follow volume changes has been recommended as the best approach in assessing respiratory and swallowing patterns (TARRANT et al, 1997).…”
Section: Introductionmentioning
confidence: 99%